2014
DOI: 10.1021/ie403507p
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Optimization Methodology for Offshore Natural Gas Liquefaction Process Design

Abstract: A simulation-based optimization framework is introduced. First, a base case design is conducted using the commercial simulator. Then, design variables are decided. Next, minimum and maximum ranges of the design variable are determined. We will call this the design space. A comprehensive simulation of the design space is executed. Next, empirical modeling of this design space is performed. This is called the process mapping step. After verification of the model using a test data set, the optimization problem is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…1) They find extensive potential applications in electrochemical energy storage and conversion, catalysis, ion exchange and molecular adsorption. 2), 3) There are various polymorphic forms of manganese dioxides including alpha (¡), beta (¢), delta (¤) and gamma (£) due to the different linkways of the primary unit [MnO 6 ] octahedra. It has been demonstrated that different structures exhibited distinct activities and thus separate application.…”
Section: Introductionmentioning
confidence: 99%
“…1) They find extensive potential applications in electrochemical energy storage and conversion, catalysis, ion exchange and molecular adsorption. 2), 3) There are various polymorphic forms of manganese dioxides including alpha (¡), beta (¢), delta (¤) and gamma (£) due to the different linkways of the primary unit [MnO 6 ] octahedra. It has been demonstrated that different structures exhibited distinct activities and thus separate application.…”
Section: Introductionmentioning
confidence: 99%
“…The movement locus for the bidirectional coupling swing consists of equations (1) and (2). When =   and A B  , equation 3turns into equation 4, which is plotted in Fig.2 Immediately before the adsorption experiment was conducted, 13X zeolite was degassed for 6 h at 553 K to remove any adsorbed species.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…For offshore natural gas production, the floating liquefied natural gas production storage and off-loading platform (LNG-FPSO) are used for offshore natural gas exploitation, pretreatment, liquefaction, storage, transportation and offloading [2][3][4][5][6][7] . The pretreatment is one of the key points of the offshore natural gas development.…”
Section: Introductionmentioning
confidence: 99%
“…Sohn and Shin(1999) 그 외에도 부유식 플랫폼, Topside 기자재 등의 설계, 실험, 검 증 등을 위해 시뮬레이션 기반 설계 기법이 도입되고 있다 (Havard, 2012;Cang et al, 2013;Song et al, 2014;Ku et al, 2014). 특히, 해양플랜트 구조물은 해양 하중, 구조물 강성, 유체 저 항력, 해양환경 등의 복합 하중이 작용하기 때문에 실제와 유사 연구가 많이 수행되고 있다 (Cha et al, 2010;Ku et al, 2014;Wang et al, 2015 (Hong, 1992;Atadan et al, 1997;Jung et al, 2012;Park et al, 2015).…”
Section: 서 론unclassified